A Review Essay on The Enlightened Economy: An Economic History of Britain 1700–1850 by Joel Mokyr - Clark, Gregory (Journal of Economic Literature, 2012)
The British Industrial Revolution is the key break in world history. Yet the timing, location, and cause of this Revolution are unsolved puzzles. Joel Mokyr's book is one of a number of recent attempted solutions. He explains the Industrial Revolution through the arrival of a particular ideology in Britain, associated with the earlier European intellectual movement of the Enlightenment. This review considers how Mokyr's “idealist” approach fares as an account of the Industrial Revolution, compared to the spate of recent proposed “materialist” explanations. (JEL N13, N63)